The Nexus between Time Management Behaviors and Work-Life Balance of Employees - Saba Shaikh; Imamuddin Khoso; Nizamuddin Channa (ETIKONOMI, 2023)
This research is envisioned to explain the impact of individual time management behaviors on the work-life balance of banking employees. Using the positivist paradigm, a self-administered survey was chosen to collect responses from bank employees across Sindh, Pakistan. The presented hypotheses were supported by quantitative analytical techniques that tested causal links between all constructs. A total of 450 questionnaires were administered, out of which 320 valid responses were analyzed using PLS-SEM. The findings validated that individual time management behaviors do contribute to attaining work-life balance in the banking sector. Results revealed a positive effect of goal setting and priorities, time management mechanics, and organization preference on employees’ work-life balance. Among all, mechanics of time management (MTM) substantially impact achieving work-life balance. This research will aid in the identification of time management practices that are better capable of balancing work and life.JEL Classification: M12How to Cite:Shaikh, S., Khoso, I., & Channa, N. (2023). The Nexus Between Time Management Behaviors and Work-Life Balance of Employees. Etikonomi, 22(1), 119–130. https://doi.org/10.15408/etk.v22i1.22385.